Hallmarks of hyperthermia in driving the future of clinical hyperthermia as targeted therapy: translation into clinical application. (2nd January 2016) - Issels, Rolf; Kampmann, Eric; Kanaar, Roland; Lindner, Lars H.
Abstract: Regional hyperthermia is described as a targeted therapy and the definitions of six hallmarks of hyperthermia are proposed, representing the pleiotropic effect of this therapeutic modality to counteract tumour growth and progression. We recommend the considerations of these hallmarks in the design of clinical trials involving regional hyperthermia as targeted therapy. Randomised clinical studies using loco-regional hyperthermia as an adjuvant to radiotherapy or to chemotherapy for locally advanced tumours demonstrate the benefit of the combination compared to either of the standard treatments alone for tumour response, disease control, and patient survival outcome. These impressive results were obtained from proof-of-concept trials for superficial or deep-seated malignancies in unselected patients. None of these trials was designed as tailored approaches for the treatment of specified targets or to select potentially more sensitive subpopulations of patients using eligibility criteria. Based upon clinical examples of targeted chemotherapy, some guidelines are described for the successful development of targeted therapeutic combinations. We also retrospectively analyse the stepwise process of generating an ongoing new clinical trial using hyperthermia as targeted therapy to evade DNA repair in combination with a DNA damaging anticancer agent to implement this new vision.